Modification of Sensor Sensitivity of Magneto-Impedancy on Multilayer [Ni80Fe20/Cu]N as result of Electro-Deposition - B. Anggit Wicaksono; Ahmad Asrori Nahrun; Nuryani Nuryani; Budi Purnama (Jurnal ILMU DASAR, 2016)
Multilayer sensor sensitivity [Ni80Fe20/Cu]N as results of electro-deposition on Cu wire has been modified by several variables; namely (i) the frequency of measurement, (ii) the number of iteration N on the system [Ni80Fe20/Cu]N, and (iii) the thickness of the spacer layer of Cu. If applied as a magnetic sensor, the measured sensor sensitivity can be calculated using the formula; ξ = 2 [(ΔZ/Z)max]/ΔH. The results of the sensitivity calculations show that the increase in the ratio of magneto-impedance directly proportional to the sensitivity of the sensor. To modify the frequency of the sample [Ni80Fe20(800nm)/Cu(300 nm)]3, the measurement sensitivity increases with increases in frequency. And the highest sensitivity is obtained 8.91%/ mT at a frequency of 100 kHz. Similar results were obtained in the variation of the number of iteration N multilayer [Ni80Fe20 (800 nm) / Cu (300 nm)]N. Senitifitas measurements at a frequency of 100 kHz and the highest number of iteration (N=5) obtained the highest sensitivity, which is 26.63%/mT. Furthermore, the sensitivity of the sensor showed a tendency to decrease with the increase in the thickness of the spacer Cu in multilayer [Ni80Fe20 (800 nm)/Cu (y nm)]3. Finally, the highest sensitivity was obtained 53.75% / mT for most thin thickness of the spacer Cu (y = 200 nm) which is the highest value in the whole of this experimentKeywords: Sensor Sensitivity, Ni80Fe20 , Frequency Measurement, Iteration Number, Spacer Cu